Available oral lipid-lowering agents could bring most high-risk patients to target: an estimate based on the Dyslipidemia International Study II-Italy. Issue 9 (September 2018) - De Ferrari, Gaetano M.; Perna, Gian P.; Nicosia, Antonino; Guasti, Luigina; Casu, Gavino; Cuccia, Claudio; Picco, Francesca; Strazzella, Caterina; Totaro, Rossana; Cercone, Stefania; Canullo, Laura; Horack, Martin; et al.
Abstract : Aims: The analysis evaluated the contemporary percentage of patients with established coronary heart disease (CHD) reaching the European guidelines recommended LDL-cholesterol (LDL-C) levels of less than 70 mg/dl and the threshold required for proprotein convertase subtlisin/kexin type 9 reimbursement in Italy (100 mg/dl). It also assessed how these percentages would change in case of diffuse use of ezetimibe. Methods: The Dyslipidemia International Study II enrolled CHD patients aged at least 18 either on lipid-lowering therapy (LLT) for at least 3 months or not on LLT at the time of the lipid profile. Distribution of LLTs and LDL-C target attainment were assessed. Multivariate logistic regression evaluated predictors of LDL-C target attainment. A 24% LDL-C lowering was modeled in patients not taking ezetimibe to assess its potential effects. Results: Among 676 Italian CHD patients enrolled, LDL-C concentrations were lower among the 631 patients (93.3%) who were on LLT (82 versus 118 mg/dl; P  < 0.001). The LDL-C target was attained by 35.4% of patients. Statin dose (median atorvastatin dose 40 mg/day) was the sole significant predictor of LDL-C target attainment. The simple addition of ezetimibe in the model reduced the percentage of patients more than 70 and 100 mg/dl from 64.6 to 37.9% and from 25.1 to 11.8%, respectively. Conclusion: Despite treatment in more than 90%, only one-third of Italian stable CHD patients attained the recommended LDL-C target. Statin dose was the sole predictor of the target achievement. The addition of ezetimibe would almost double patients at target and halve the potential candidates for reimbursement of more expensive agents such as proprotein convertase subtlisin/kexin type 9 inhibitors.